2022
DOI: 10.3389/fpubh.2021.758874
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Prevalence and Risk Factors Among Patients With Cardiovascular Diseases in Post-COVID-19 China

Abstract: Objective: Data are limited on the psychological disorders of patients with cardiovascular disease during the post-COVID-19 period, although mental health status is associated with morbidity and mortality. We aimed to investigate the prevalence of anxiety and depression and risk factors among patients with cardiovascular disease in the post-pandemic period.Method: A cross-sectional survey was conducted through opportunistic and snowball sampling in southeast China from 10 October to 24 November. Anxiety and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
4
12
1
3
Order By: Relevance
“…In the fsQCA model, depression is identified as a conditional variable that predict the level of sleep quality. Our findings are consistent with recent studies which suggested sociodemographic factors and internal factors such as depression are strong predictors of sleep quality (Ma et al, 2020; Wu et al, 2022; Zhang et al, 2022). In general, the results of both methods (regression and fsQCA model) indicated that gender, age, and depression level are strong predictors of patients’ sleep quality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the fsQCA model, depression is identified as a conditional variable that predict the level of sleep quality. Our findings are consistent with recent studies which suggested sociodemographic factors and internal factors such as depression are strong predictors of sleep quality (Ma et al, 2020; Wu et al, 2022; Zhang et al, 2022). In general, the results of both methods (regression and fsQCA model) indicated that gender, age, and depression level are strong predictors of patients’ sleep quality.…”
Section: Discussionsupporting
confidence: 93%
“…Current international guidelines recommend the use of Patient Health Questionnaire 9 (PHQ-9) and the 7-item Generalized Anxiety Disorder Scale (GAD-7) to screen for depressive and anxious symptoms. A 2022 survey showed that among Chinese CVD patients, the occurrence of anxiety and depression was 11.72% and 9.2%, respectively (Wu et al, 2022). Depressive and anxious symptoms can be expressed differently in different populations around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries adopted a policy of lockdown aiming to decelerate the contagion, which subsequently made dramatical changes of the daily lifestyle of the residents, and negatively influenced the mental health of individuals (19,20). Recent studies implicated that outbreak of COVID-19 was supposed to cause emotional disorders, cognition dysfunction, behavioral disturbance and impaired quality of life, especially in population with psychosomatic diseases such as coronary heart disease, irritable bowel disease and psoriasis, in whom psychological distress and somatic diseases could mutually influence one another (21)(22)(23)(24). Regarding dentistry, most of the studies indicated adverse effects of COVID-19 on psycho-emotional status (stress, anxiety, depression), which lead to the intensification of TMD symptoms and increased orofacial pain (OFP) (25).…”
Section: Introductionmentioning
confidence: 99%
“…Распространенность психоэмоциональных расстройств среди пациентов с ФП значительна и по некоторым данным превышает 30% [33]. При этом к наиболее распространенным среди пациентов с ФП относятся депрессивные (до 38%) и тревожные (до 35%) нарушения, а также тяжелые психические расстройства (шизофрения, биполярное аффективное расстройство) -до 15-18% [34][35][36].…”
Section: психоэмоциональные расстройстваunclassified